X-ray photoelectron spectroscopy analysis of chemically modified halloysite. (October 2020) - Kubala-Kukuś, A.; Szczepanik, B.; Stabrawa, I.; Banaś, D.; Szary, K.; Pajek, M.; Rogala, P.; Wójtowicz, K.; Słomkiewicz, P.
Abstract: The influence of activation temperature on the structure of halloysite mineral (HM) from the "Dunino" strip mine (Poland), activated with 25 wt% sulfuric(VI) acid, was investigated using a surface sensitive X-ray photoelectron spectroscopy (XPS) method. XPS measurements were performed for commercially available halloysite nanoclay (HNT), raw halloysite mineral (HS) directly from the mine and samples of a halloysite mineral (HM) activated at different temperatures up to 100 °C. The XPS spectra were measured in wide range of the electron binding energy (survey spectra) and in the region of O, Al and Si photoelectron peaks (detailed spectra). Changes of photoelectron peak positions and their intensities are discussed as a function of activation temperature. Elemental composition of HS, HM and HNT surfaces was estimated and compared with bulk results obtained using the wavelength dispersive X-ray fluorescence (WDXRF) method. Concentration changes of O, Al, Si and Fe obtained by both XPS and WDXRF measurements are discussed. An increase of the silicon to aluminum ratio (Si/Al), as a result of higher activation temperature, is demonstrated. Abstract : Highlights: XPS study of activation temperature influence on the halloysite mineral structure. Changes of photoelectron peak positions and their intensities are discussed. Elemental composition of sample surfaces (XPS) compared with bulk results (WDXRF). Higher activation temperature results in increase of the Si/Al ratio.